Land Reform Sebagai Gerakan Pemerataan dalam Penguasaan, Pemilikan, Penggunaan dan Pemanfaatan Lahan Pertanian - Riki Desriandi; Selma Ayu Lestari; Adi Wandani; Nurbaiti; Dea Maulisna; Indra Muchlis Adnan; Didi Syaputra (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2024)
In an effort to improve the well-being of agricultural workers, Land reform aims to restore a sense of fair control, ownership and use of land. However, as a matter of fact, this objective was not understood on the grounds that the land object had been moved to one more party before it was effectively circulated. Accordingly, settlement endeavors are expected to stay away from the issue of adding land protests rashly. The Essential Agrarian Regulation (UUPA) is the principal land change program in Indonesia. Land change is characterized as an adjustment of the design of command over land possession, in a simply political sense as well as from a specialized perspective. The objective of the LoGA is to roll out crucial improvements to existing agrarian relations with the goal that they become all the more and satisfy the interests of the worker individuals. The reason for land change being done in Indonesia is to build the pay and way of life of the cultivators of the land, as a premise or essential for completing monetary improvement towards a fair and prosperous society in view of Pancasila. To accomplish this objective, it is completed by holding a fair dissemination of the vocations of the laborer individuals as land and a fair circulation of results, executing the rule of land for ranchers, finishing the property manager agricultural workers, and safeguarding against a powerless economy.